Report of Mr. Eugene Gorman on the Problem of Hungary - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Eugene Gorman The report written by Mr. Eugene Gorman, representative of the Government of Australia on the Hungarian situation.